2013
DOI: 10.1089/jwh.2012.3590
|View full text |Cite
|
Sign up to set email alerts
|

Patient Barriers to Follow-Up Care for Breast and Cervical Cancer Abnormalities

Abstract: Background: Women with breast or cervical cancer abnormalities can experience barriers to timely follow-up care, resulting in delays in cancer diagnosis. Patient navigation programs that identify and remove barriers to ensure timely receipt of care are proliferating nationally. The study used a systematic framework to describe barriers, including differences between African American and Latina women; to determine recurrence of barriers; and to examine factors associated with barriers to follow-up care. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
86
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 57 publications
(62 reference statements)
5
86
1
Order By: Relevance
“…These findings support our previously published analyses documenting the relationship between multiple social service barriers, such as lack of adequate housing or income supports, and timely resolution. 28 Half of our navigated population had documented barriers to care, similar to some navigation programs 17,27 while other navigation programs have found a greater frequency of barriers 29 using the same methodology in barrier identification. Such differences between sites reinforces the importance of tailoring navigation training and implementation to the local needs and barriers of the community served.…”
Section: Discussionmentioning
confidence: 67%
“…These findings support our previously published analyses documenting the relationship between multiple social service barriers, such as lack of adequate housing or income supports, and timely resolution. 28 Half of our navigated population had documented barriers to care, similar to some navigation programs 17,27 while other navigation programs have found a greater frequency of barriers 29 using the same methodology in barrier identification. Such differences between sites reinforces the importance of tailoring navigation training and implementation to the local needs and barriers of the community served.…”
Section: Discussionmentioning
confidence: 67%
“…Previous research has found that having at least one barrier to care significantly increases the chance of loss to follow-up. 9,10 PN has been shown to reduce barriers, 23,24 as well as loss to follow-up. 25 Thus, knowing who is more likely to have a barrier to recommended care can allow medical facilities to direct scarce PN resources to those patients, increasing compliance with CoC mandates while improving the receipt of timely and quality care.…”
Section: Discussionmentioning
confidence: 99%
“…That patient-focused barriers to care (which included comorbidities and fear 23 ) affected diagnostic resolution in patients with breast abnormalities was not surprising because those patients were more likely to have comorbidities and fear is a common finding in patients with abnormal breast tests or clinical findings. 3,26 In patients with cervical abnormalities, it is likely that other-focused barriers affected resolution because that barrier grouping included issues related to employment and child care. Those issues are likely more problematic for younger patient populations, such as the patients with cervical abnormalities in this study.…”
Section: Discussionmentioning
confidence: 99%